A Comparison of Supreme Court Justices’ Legal Argumentation in Deciding Disputes on Transfer Pricing Management Fees in Indonesia - Agus Suharsono; Nanik Prasetyoningsih; Nur Aida Ikrima (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of the Study: to of the Supreme Court Justice in deciding transfer pricing disputes related to the payment of management fees in Indonesia so that tax authorities and taxpayers understand its implementation to prevent similar cases. Methodology: This doctrinal research using statutory, conceptual, cases, and interpretive approaches; The data is secondary, namely laws, Supreme Court decisions, and concepts in relevant literature. Results:  The Supreme Court Justice's argument in deciding the management fee transfer pricing law and existing law in the international community, evidence, and the judge's knowledge of legal philosophy, legal principles and previous decisions. Taxpayers must document all evidence of transactions and conduct functional analysis by Arm's Length Principle to prove the correctness of payment of management fees. Applications of this study: Taxpayers and tax authorities can understand the argument of the Supreme Court Justice in deciding the dispute over transfer pricing management fees to be considered in making laws and regulations implementing it, and encourage further research by comparing in other countries. Novelty: Substantive truth is the primary basis for the Supreme Court Justice's argument in the transfer pricing management fee dispute. Keywords: Legal Argumentation; Management Fee; Supreme Court; Tax-Payers; Transfer Pricing.   ABSTRAK Tujuan: menganalisis argumentasi Hakim Agung dalam memutus sengketa transfer pricing terkait pembayaran management fee di Indonesia, agar otoritas pajak dan wajib pajak memahami implementasinya untuk mencegah ada kasus serupa. Metodologi: Penelitian doktrinal ini menggunakan pendekatan perundang-undangan, konsep, dan interpretasi, datanya berupa undang-undang, putusan Mahkamah Agung, dan studi pustaka yang relevan. Temuan: Argumentasi Hakim Agung dalam agung dalam memutus sengketa transfer pricing management fee  mengutamakan kebenaran substansif, berdasarkan hukum positif tertulis maupun hukum yang hidup dalam masyarakat internasional, alat bukti, serta pengetahuan hakim tentang filsafat hukum, asas hukum, dan putusan sebelumnya. Wajib pajak harus mendokumentasikan semua bukti transaksi dan melakukan analisis fungsional sesuai Arm's Length Principle untuk membuktikan kebenaran pembayaran management fee. Kegunaan: wajib pajak dan otoritas pajak dapat memahami argumentasi Hakim Agung memutus sengketa transfer pricing management fee, untuk dipertimbangan dalam membuat undang-undang dan peraturan pelaksananya, serta mendorong penelitian lanjutan dengan membandingkan di Negara lain. Kebaruan: Kebenaran substantif lebih diutamakan oleh Hakim Agung dalam menyususun argumentasi putusan sengketa transfer pricing management fee. Kata Kunci: Argumentasi Hukum; Management Fee; Mahkamah Agung; Wajib Pajak; Transfer Pricing